2021
DOI: 10.1186/s12301-021-00233-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enhanced recovery after surgery protocol and conventional approach after laparoscopic transperitoneal radical prostatectomy: a retrospective analysis

Abstract: Background Although open radical prostatectomy has been used in the treatment of localized prostate cancer for a long time, minimally invasive surgical approaches such as laparoscopic radical prostatectomy and robot-assisted radical prostatectomy have recently gained importance in order to improve postoperative results and shorten hospital stay. Although the enhanced recovery after surgery (ERAS) protocol was first defined for gastrointestinal surgeries in 2001, it has now been used in gynecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Open surgical enucleation, performed either via a suprapubic (transvesical) or retropubic approach, has traditionally been the recommended technique for GPH. More recently, laparoscopic and robotic simple prostatectomy have emerged as less invasive alternatives and are considered less invasive compared to open simple prostatectomy [ 10 , 11 ]. Studies have shown that minimally invasive approaches offer promising results, associated with less postoperative catheter time, a shorter hospital stay, fewer complications, and favorable results compared to open prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgical enucleation, performed either via a suprapubic (transvesical) or retropubic approach, has traditionally been the recommended technique for GPH. More recently, laparoscopic and robotic simple prostatectomy have emerged as less invasive alternatives and are considered less invasive compared to open simple prostatectomy [ 10 , 11 ]. Studies have shown that minimally invasive approaches offer promising results, associated with less postoperative catheter time, a shorter hospital stay, fewer complications, and favorable results compared to open prostatectomy.…”
Section: Discussionmentioning
confidence: 99%